Reform of Private International Law in Countries Successors of the Former Yugoslavia New Legal Challenges v. Legal Tradition - Šaula, Valerija E. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Countries successors of the former Socialist Federal Republic of Yugoslavia have achieved an immense progress in reforming their legal systems, despite unfortunate war consequences. The ratio behind this process is, firstly, to adhere to the new international obligations (especially European Convention for the Protection of Human Rights and Fundamental Freedoms). Secondly, to adjust, as far as possible, to the European Union law (acquis communaitaire). One of the similarities of all these countries is the clear intention to reform their Private International Law. In the era of globalization, wide circulation of persons, goods, services, foreign judicial and arbitral decisions and other public documents, conflict of law rules and rules on international jurisdiction in private law relations are becoming more and more important in daily life and legal practice. There is a strong need for regional harmonization of the rules of Private International Law. There is also a need for specific expertise in this field of law, perhaps specialization of judges who would also train other colleagues, in order to have a coherent, consistent and stabile legal system and to enjoy respect in international community. This paper will focus on Private International Law reform in the countries successors of the former SFRY. It will try to show that it is possible to reconcile the need to do the extensive legal reform but also to retain the basic principles of the former joint legal tradition.